Synaptopodin is necessary for Shigella flexneri intercellular spread - Vickery, Jenna M; Toperzer, Jody D; Raab, Julie E; Lenz, Laurel L; Colgan, Sean P; Russo, Brian C (bioRxiv, 2023)
For many intracellular pathogens, their virulence depends on an ability to spread between cells of an epithelial layer. For intercellular spread to occur, these pathogens deform the plasma membrane into a protrusion structure that is engulfed by the neighboring cell. Although the polymerization of actin is essential for spread, how these pathogens manipulate the actin cytoskeleton in a manner that enables protrusion formation is still incompletely understood. Here, we identify the mammalian actin binding protein synaptopodin as required for efficient intercellular spread. Using a model cytosolic pathogen, , we show that synaptopodin contributes to organization of actin around bacteria and increases the length of the actin tail at the posterior pole of the bacteria. We show that synaptopodin presence enables protrusions to form and to resolve at a greater rate, indicating that greater stability of the actin tail enables the bacteria to push against the membrane with greater force. We demonstrate that synaptopodin recruitment around bacteria requires the bacterial protein IcsA, and we show that this recruitment is further enhanced in a type 3 secretion system dependent manner. These data establish synaptopodin as required for intracellular bacteria to reprogram the actin cytoskeleton in a manner that enables efficient protrusion formation and enhance our understanding of the cellular function of synaptopodin. Intercellular spread is essential for many cytosolic dwelling pathogens during their infectious life cycle. Despite knowing the steps required for intercellular spread, relatively little is known about the host-pathogen interactions that enable these steps to occur. Here, we identify a requirement for the actin binding protein synaptopodin during intercellular spread by cytosolic bacteria. We show synaptopodin is necessary for the stability and recruitment of polymerized actin around bacteria. We also demonstrate synaptopodin is necessary to form plasma membrane structures known as protrusions that are necessary for the movement of these bacteria between cells. Thus, these findings implicate synaptopodin as an important actin-binding protein for the virulence of intracellular pathogens that require the actin cytoskeleton for their spread between cells.